Conceptual Type - a commentary on the Internet's design development?. Issue 1 (1st December 2013) - Engholm, Ida
Ida Engholm's contribution to the conference Conceptual Type – Type led by ideas, Copenhagen, 19. November 2010.Where are the idealistic fonts, the artsy fonts, the non fonts, the political fonts, the funny fonts, the difficult fonts, the fonts that do not look like fonts, fonts that are frontiers of new belief?We would like to focus on the ideas and concepts behind type. Rather than talk about type by asking who made it and what does it look like, we will start a new decade by asking why do we make it and what does it mean?In conceptual art the idea or concept is the most important aspect of the work. When an artist uses a conceptual form of art, it means that all the planning and decisions are made beforehand and the execution is a perfunctory affair. The idea becomes a machine that makes art.'Sol LeWitt. 'Paragraph on Conceptual art', Artforum, 1967.We would like to borrow from Sol LeWitt's vision and replace 'art' with 'type', looking for the idea-type-machines of our time.[From the conference call]